PENGARUH PARTISIPASI PENGANGGARAN, MOTIVASI KERJA, KOMPENSASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL (Studi Kasus pada Kepala Bagian di PT Jauwhannes Traco se Jawa) (Students' Journal of Accounting and Banking, 2013)
This study aims to determine the significance of the effect of budgetary participation, motivation, compensation and job satisfaction on organizational commitment on all head of PT Jauwhannes Traco. The study also examines effect of budgetary participation, motivation, compensation and job satisfaction on organizational commitment.Samples from this study were all head of PT Jauwhannes Traco. The data used in this study comes from the perception of all heads of sections PT Jauwhannes Traco collected using questionnaires. From 65 questionnaires were delivered to all parts of the head PT Jauwhannes Traco, a total of 37 questionnaires were successfully re-complete and can be processed. The questionnaire was then tested using the Test Validity and Reliability Test. The data collected were processed using multiple linear regression analysis after previously tested using the Classical Test assumptions. For Model Test using Adjusted R Square and Test F , whil e for Hypothesis Testing using the t test. Results of this study indicate that there is a positive and significant effect between budget ary participation, motivation, compensat ion and satisfaction work on organizational commitment.Keywords: Participation in Budgeting, Work Motivation, Compensation, Job Satisfaction and Organizational Commitment.